Direct Oral Anticoagulants after Ischemic Stroke: Which Patient? Which Drug? And How Early? - De Marchis, Gian Marco (Hämostaseologie, 2021)
Direct oral anticoagulants (DOACs) are recommended over vitamin K antagonists (VKAs) in patients with atrial fibrillation (AF) and ischemic stroke. The main advantage of DOAC over VKA is the lower rate of bleeding and mortality. This review covers challenges clinicians can encounter when treating patients with AF and ischemic stroke, including timing of DOAC start and ongoing randomized clinical trials, appropriate dosing, and available comparative evidence across DOACs. For patients without AF but with an ischemic stroke, the review outlines the role of DOACs. Finally, the risk of thrombotic events associated with specific DOAC reversal agents and DOAC pausing is reviewed.
Keywords: stroke; atrial fibrillation; anticoagulation; timing